(untitled) (Global Journal of Management and Business Research, 2022)
This study examines the impact of inflation on unemployment in Nigeria from 1985 to 2019. In analyzing the data, nonlinear autoregressive distributive lag (NARDL) was employed. The result of the nonlinear ARDL shows that in the short-run inflation (positive) has a negative and significant effect on unemployment while inflation (negative) has a positive and significant impact on unemployment. Similarly, in the long run, inflation (positive) has a negative and significant effect on unemployment. The study concludes that there is a piece of empirical evidence for the existence of the nonlinear Phillips curve in Nigeria, within the period of the study. It is recommended that the government should reduce the positive rise in price by implementing policies that encourage production. An increase in agricultural production for example increases the level of employment which has great potential to boost food supply and reduce the level of inflation and unemployment in the economy. In addition, the study identifies the benefits and inherent potentials in natural resources in Nigeria that can be harnessed to address the problem of inflation and unemployment.